Day 1 Tue, October 20, 2015 2015
DOI: 10.2118/175928-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation Approach to Modelling and Understanding Fracture Geometry with Respect to Well Spacing in Multi Well Pads in the Duvernay – A Case Study

Abstract: Hydraulic fracturing in multi stage horizontal unconventional wells is perhaps one of the most important if not the most important in the drilling and completion cycle of these wells. It's also the most applied technique repeatedly in multiple formations throughout the world and yet the question that looms large over us, do we understand the fracture geometry in these unconventional environments.Year on year most unconventional formations seem to fall in line with the industry trend of increasing lateral lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The HFM results presented in this study (Fig. 6, 9) are similar to complex hydraulic fracture networks simulated in the Duvernay Formation and reported earlier (Ramanathan et al 2015;Ferrer et al 2020). Based on the results of HF simulations with DFN-1 (Case 1) and DFN-2 (Cases 2 and 3) of this study (Fig.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The HFM results presented in this study (Fig. 6, 9) are similar to complex hydraulic fracture networks simulated in the Duvernay Formation and reported earlier (Ramanathan et al 2015;Ferrer et al 2020). Based on the results of HF simulations with DFN-1 (Case 1) and DFN-2 (Cases 2 and 3) of this study (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Numerical simulations studies have shown that presence of natural fractures in a formation impacts hydraulic fracture propagation resulting in complex HFs-NFs networks (Weng et al 2011;Wu et al 2012;Haege et al 2015;Weng 2015;Rutqvist et al 2018). The fracture network complexity contributes to the efficiency of hydraulic fracturing operations in unconventional reservoirs (Ramanathan et al 2015;Ferrer et al 2020;Li et al 2020). Additionally, fluid pressure transmission through complex HFs-NFs networks in tight fractured formations may result in shear slip reactivation of critically-stressed faults and induced seismicity.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches include the consideration of geomechanics [11] and microseismic analysis [12], but these face the issues of inadequate data, due to high data acquirement costs and extra uncertainty, which is especially observed in the noisy microseismic data. Extensive analytical and numerical simulation approaches have been conducted for the well spacing problem by various authors [13][14][15], since it is relatively cheap. However, these simulations rarely consider the subsurface uncertainties associated with the fractures.…”
Section: Introductionmentioning
confidence: 99%